PERKEMBANGAN INTELEKTUALISME KEAGAMAAN DI NUSANTARA - Rusli, Risan; herwansyah, Herwansyah; Toharuddin, Toharuddin (Program Studi Studi Agama Agama Fakultas Ushuluddin dan Pemikiran Islam, 2020)
Islam is rahmatan Lil 'Alamin, the universal religion. It means that its mission and teachings are not only for one group or country but all men. However, the meaning of the universality of Islam among Muslims is not uniform. Some group defines that the teachings of Islam brought by the Prophet Muhammad based Arabic culture are final, so this must be taken as granted as they are. Some groups also interpret the universality of Islamic teachings as being not limited to time and place. Hence it can blend into any culture. The first group has the ambition to uniform all Islamic cultural-based into one, as practiced by the Prophet Muhammad. They don't accept any particularity. This group is called fundamentalist. However, the second group considers that Islam is a value that can adapt to all existing cultures. Islam lies in its value, not its physical form. This group is called the substantive group. However, apart from both, another group reckons some Islamic value is fundamental and can not adjust to cultures.